2003
DOI: 10.1038/sj.onc.1206645
|View full text |Cite
|
Sign up to set email alerts
|

Members of the poly (rC) binding protein family stimulate the activity of the c-myc internal ribosome entry segment in vitro and in vivo

Abstract: The 5 0 untranslated region of the proto-oncogene c-myc contains an internal ribosome entry segment and c-Myc translation can be initiated by cap-independent as well as cap-dependent mechanisms. In contrast to the process of cap-dependent initiation, the trans-acting factor requirements for cellular internal ribosome entry are poorly understood. Here, we show that members of the poly (rC) binding protein family, poly (rC) binding protein 1 (PCBP1), poly (rC) binding protein 2 (PCBP2) and hnRNPK were able to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
182
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(187 citation statements)
references
References 39 publications
3
182
1
1
Order By: Relevance
“…Cytoplasmic localization of hnRNP K is required for BCR/ABL oncogenic activity in chronic myelogenous leukemia (Notari et al, 2006), and has been shown to promote cellular migration in fibrosarcoma cells (Inoue et al, 2007). Cytoplasmic hnRNP K also regulates posttranscriptional activity; it has been shown to directly stimulate IRES-dependent c-myc translation (Evans et al, 2003;Notari et al, 2006) and stabilize the gastrin mRNA . Accordingly, cytoplasmic hnRNP K may elevate tumorigenic potential by altering the expression of its target genes at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoplasmic localization of hnRNP K is required for BCR/ABL oncogenic activity in chronic myelogenous leukemia (Notari et al, 2006), and has been shown to promote cellular migration in fibrosarcoma cells (Inoue et al, 2007). Cytoplasmic hnRNP K also regulates posttranscriptional activity; it has been shown to directly stimulate IRES-dependent c-myc translation (Evans et al, 2003;Notari et al, 2006) and stabilize the gastrin mRNA . Accordingly, cytoplasmic hnRNP K may elevate tumorigenic potential by altering the expression of its target genes at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…The tumorigenic activity of hnRNP K is conferred through its ability to increase proliferation (Lynch et al, 2005), clonogenic potential (Notari et al, 2006) and metastasis (Inoue et al, 2007). These effects may be due, at least in part, to the ability of hnRNP K to upregulate c-myc expression through the c-myc internal ribosome entry segment (IRES; Evans et al, 2003;Notari et al, 2006). hnRNP K is a nucleocytoplasmic shuttling protein and primarily located in the nucleus (Michael et al, 1997); however, cytoplasmic accumulation of hnRNP K via ERKmediated phosphorylation of hnRNP K serine-284 and -353 has been reported in cervical carcinoma HeLa cells (Habelhah et al, 2001) and chronic myelogenous leukemia cells (Notari et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These factors bind to RNA at specific sites in the 5 0 -UTR and induce conformational changes that facilitate recruitment of the ribosome to the IRES (Stoneley et al, 2000;Evans et al, 2003). Thus, one possible explanation for AKT's regulatory role is that it affects expression or binding of specific ITAFs to the VEGF IRES.…”
Section: Discussionmentioning
confidence: 99%
“…In combination with PCBP1, these interact specifically with regions of the c-myc IRES, and increase internal translation initiation. 61,62 Since c-myc translation also occurs via cap-dependent initiation, the 5 0 UTR needs to be sufficiently flexible to allow ribosome scanning to the initiation AUG. The ITAFs in this case may be required to hold the RNA in the correct conformation for internal recruitment of the ribosome.…”
Section: Analysis Of Mrnas That Remain Polysomally Associated During mentioning
confidence: 99%